2012
DOI: 10.3109/03014460.2012.681802
|View full text |Cite
|
Sign up to set email alerts
|

Natural selection among coastal populations of India: Trend and extent

Abstract: There is a significant difference in the extent and process of natural selection among coastal and non-coastal populations. Mortality is playing a greater role in the total selection intensity of coastal populations, although the trend is declining in the entire region and reversal in the roles of I(m) and index of fertility (I(f)) is witnessed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
3
1
Order By: Relevance
“…The contribution of fertility component to total selection index in current study is higher than the earlier study of coastal populations study by Kapoor et al in 2012. Their study among the populations of Goa and Odisha shows the fertility component contribution of 66.23% while present study estimate is of 69.54% (Table -3). Similarly, there is a decrease in the embryonic mortality component contribution (9.92%) as compared to their study (13.95%) and there is slight increase in the post-natal mortality component contribution (19.82%earlier to 20.54%-present).…”
Section: Resultscontrasting
confidence: 79%
See 1 more Smart Citation
“…The contribution of fertility component to total selection index in current study is higher than the earlier study of coastal populations study by Kapoor et al in 2012. Their study among the populations of Goa and Odisha shows the fertility component contribution of 66.23% while present study estimate is of 69.54% (Table -3). Similarly, there is a decrease in the embryonic mortality component contribution (9.92%) as compared to their study (13.95%) and there is slight increase in the post-natal mortality component contribution (19.82%earlier to 20.54%-present).…”
Section: Resultscontrasting
confidence: 79%
“…The coastal vulnerability is induced both by human related causes like rise in greenhouse gas (Nicholls et al 1999;Varekamp 1999) and natural factors like season change. So far, the study among the coastal part of India (Odisha and Goa) is conducted by Kapoor et al in 2012 which reveals that mortality is predominant factor contributing to selection intensity among coastal populations (Kapoor et al, 2012) whereas fertility is predominant factor among Non-coastal populations (Singh and Kapoor, 2015). Hence, the present investigation was to determine the variation in selection intensities among populations of two states of western coast of India i.e., Gujarat and Maharashtra.…”
Section: Introductionmentioning
confidence: 99%
“…The fertility component percent of the eastern coast varies from 31.6 for Jalari of Odisha (Reddy, 1983) to 81.7 for Palli of Odisha. The mortality component percent varied from 24.5 for Jalari of Odisha (Kapoor et al, 2012) to 72.2 for Mallia of Odisha. However, for all the population groups of western coasts (Figure 3), the percentage of fertility component exceeds 60 percent, which contributed more to the total selection index (I), that is, I t or I 2 than the mortality component, which did not exceed 35 percent.…”
Section: Discussionmentioning
confidence: 99%
“…All these research works showed a relationship between socioeconomic conditions and the index of total selection on the above-mentioned geo-climatic regions, except the coastal areas, which have not been studied to its core. Kapoor et al (2012) conducted a study on coastal areas and their geo-climate dimensions, which reported that mortality is a predominant factor contributing to selection intensity. Fisher (1930), Wright (1938), and Basu (1969) suggested that fertility and mortality components are directly responsible for the rate and direction of human evolution.…”
Section: Introductionmentioning
confidence: 99%